Global habits, habit differentials, and international macroeconomic adjustment to income shocks - Shinsuke Ikeda; Ichiro Gombi (Osaka University, Institute of Social and Economic Research (ISER), 2010)
In a two-country model with habit formation, we focus on interdependent macroeconomic adjustments to global and country-specific income shocks.Global habits and habit differentials play key roles in the global equilibrium dynamics, possibly nonmonotonic, and in the determination of international asset distribution. A country's steady-state holdings of net external assets rely on (i) weighted income difference in excess of habit differentials and (ii) global income in excess of global habits. Local income shocks have greater effects on the international asset distribution than global income shocks. With habit formation, positive income shocks lower the world interest rate, thereby harming the creditor country and benefitting the debtor country due to the intertemporal terms-of-trade effect. In contrast to the case of trade theory, this intertemporal immiserizing growth effect is more likely to be caused by global income shocks than by country-specific income shocks.
Keywords: F41; D90; 330; global habits; habit differentials; immiserizing growth; two country model; global shock; country-specific shock; Wirtschaftswachstum; Schock; Wirtschaftliche Anpassung; Zwei-Länder-Modell; Theorie